Laser therapy in the treatment of temporomandibular disorders (Research, Society and Development, 2022)
Temporomandibular disorders are a group of pathologies that involve the temporomandibular joint. This group of dysfunctions has a multifactorial causal factor, in many cases it is associated with parafunctional habits or even emotional issues, such as stress. The manifestations are pain in the condylar region that can spread to a headache, tinnitus and vertigo. However, there are currently several therapeutic resources, such as muscle relaxant plates, surgeries or non-invasive means such as low-level laser. However, it requires a multidisciplinary approach, involving professionals such as speech therapists, psychologists, physiotherapists and dentists. The objective of this work was to investigate laser therapy applied to TMD through a literature review. Therefore, it was carried out through searches in the Google Scholar, Lilacs, BBO and PubMed databases. Thus, the current literature cites that laser therapy is effective and has analgesic and anti-inflammatory action. In addition, the cause of temporomandibular disorder is often associated with malocclusion. In some recent articles, it is discussed that low-level laser therapy has a regenerative character of cells and its use is effective in the treatment of temporomandibular disorders. Based on these researches, it was evidenced that the low-level laser brings positive repercussions to the treatment of the patient, having the main indication of the use associated with other therapies.